Flexibility for Who? Working Time, the Ontario Employment Standards Act and the Experiences of Workers in Low-Wage and Precarious Jobs: De la flexibilité pour qui? Loi sur les normes du travail de l’Ontario et temps de travail : expérience de travailleurs à bas salaire et occupant des emplois précaires - Thomas, Mark; Condratto, Shelley; Landry, Danielle; Steedman, Mercedes (Relations industrielles / Industrial Relations, 2020)
In Ontario, hours of work and overtime standards are regulated by the Employment Standards Act (ESA). This legislation covers most employers and employees in the province. As part of an ESA reforms process designed to promote workplace flexibility and enhance competitiveness, the Ontario ESA (2000) allowed for the extension of weekly maximum hours from 48 to 60, and the calculation of overtime pay entitlements to be based on an averaging of hours of work over up to a four-week period.Situated in the context of shifts towards greater working time flexibility, this paper examines the dynamics of working time regulation in the Ontario ESA, with a specific focus on the regulation of excess and overtime hours. The paper considers these processes in relation to general trends towards forms of labour market regulation that support employer-oriented flexibility and that download the regulation of employment standards to privatized negotiations between individual employees and their employers, tendencies present in the ESA that were sustained through further reforms introduced in 2018 and 2019.The paper draws its analysis from interviews with both workers in precarious jobs and Employment Standards Officers from the Ontario Ministry of Labour (MOL), as well as administrative data from the MOL and archival records. In the general context of the rise of precarious employment, the paper argues that ESA hours of work and overtime provisions premised upon creating working time flexibility enhance employer control over time, exacerbate time pressures and uncertainty experienced by workers in precarious jobs, and thereby intensify conditions of precariousness. The article situates the working time provisions of Ontario’s ESA in the context of an ongoing fragmentation of the regulation of working time as legislated standards are eroded in ways that make workers in precarious jobs more vulnerable to employer exploitation.